Vertical transmission of SARS-CoV-2: a brief literature review - Mounir, Moukit; Ouardi, Assia El; Babahabib, Abdellah; Hassani, Mehdi El; Kouach, Jaouad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
As COVID-19 virus is still spreading, more infections in pregnant women are likely to be seen. At this time, very little is known about vertical transmission of SARS-COV-2 from infected pregnant woman to her infant. Authors reviewed the risk of vertical transmission of COVID-19 by using data of published articles and official websites up to May 11, 2020. The searches revealed 16 articles (12 case reports/series and 4 retrospective studies) collectively comprising 194 infected pregnant women with COVID-19. 140 cases of neonates delivered from pregnant women with COVID-19 were collected. The SARS-COV-2 nucleic acid test, in day 2, was positive in 4 newborns. Based on limited data, there is no evidence for vertical transmission of COVID-19. Some studies suggestive of maternal-fetal transmission deserve careful evaluation before a definitive finding.